PENGARUH DIABETIK SELF MANAGEMENT EDUCATION (DSME) TERHADAP RESIKO TERJADINYA ULCUS DIABETIK - Azissah, Danur (JURNAL MEDIA KESEHATAN, 2018)
The sufferers’ incapable in carried out DM type 2 is one of the most caused it. Diabetic Self- Management Education (DSME) is the method which can stimulate of patients’ knowledge; skill and ability in doing the self-care for prevent the ulcers’ diabetic. The aim of this research is to find out the influence of DSME toward the risk of consistence of ulcers’ diabetic for path treatment’s patients of mellitus diabetes (MD) type 2 at Pukesmas Jalan Gedang of Bengkulu’s working area in year 2016. The method of this research is quasi-experimental with pre-test and post-test approach. Simple Random Sampling is used to divided the 66 respondent in 2 groups i.e. intervention and control groups. The result showed that the influence of DSME toward risk of consistence of ulcers’ diabetic before DSME (p=0,329) whereas, after DSME (p=0,020); with improvement of knowledge before DSME (p=0,135),after DSME (p=0,027); and leg treatment behavior before DSME (p=0,135) whereas, after DSME (p=0,041); as well as self-confidence before DSME (p=0,454) whereas, after DSME (p=0,002) by value (??=0,05). It can conclude that there is a significant influence of DSME toward risk of consistence of ulcers’ diabetic for path treatment’s patients of mellitus diabetes (MD) type 2 at Pukesmas Jalan Gedang Bengkulu’s Working Area in year 2016. This research can be input information for the health’s staff. In order, it can give the knowledge and the health promotion about the influence of DSME toward the risk of consistence of ulcers’ diabetic.